SIXTH ANNUAL CONFERENCE U. S. FIRE ADMINISTRATION SAN FRANCISCO, CAL. JAN. 19-21, 1981 (810119-810121). SESSION ON TECHNOLOGY FOR PREVENTION OF RESIDENTIAL FIRES. ""SELF- EXTINGUISHING CIGARETTES - A CONGRESSIONAL CHALLENGE"". (Tufts Archival Research Center, 2007)
Marginalia; Transcription of a presentation on "Self-Extinguishing Cigarettes- A Congressional Challenge" given at the United States Fire Administration's Sixth Annual Conference on Technology for Prevention. Discusses the brief history behind cigarette started fires and attempts to regulate cigarette safety. Reveals the mechanism behind cigarette-started fires as well as how cigarettes can be changed to be self-extinguishing. Specifically addresses the Cigarette Safety Act, a newly introduced bill. Challenges the tobacco lobby to refute claims about cigarette-started fires. Summarizes grassroots work on the bill.